Traces of Technological Well-being: Digi-uplifters and Digi-downshifters - Tuuli Turja; Jari Hakanen; Oxana Krutova; Pertti Koistinen (Nordic Journal of Working Life Studies, 2023)
Digitalization adds demands to contend with technological developments for both employees and organizations. At the same time, technological changes transform work to become more intensive and hectic. This study examined determinants of technological well-being after digitized work. Technological well-being was operationalized as Digi-downshifting where decreased workload associates with job satisfaction and as Digi-uplifting where increased workload associates with job satisfaction. A subsample (N = 3321) of workers at digitalized workplaces from the Finnish Quality of Work Life Survey was used in mean comparisons and binary logistic regression analysis. Digi-uplifters emerged as the most predominant profile among categories of technological well-being and ill-being. Extensive working time with technologies and employees’ influencing opportunities at the workplace stood out as the most consistent determinants of technological well-being. Thus, Nordic countries with skilled, technologically oriented workforce and democratic working cultures have particular promise in fostering Digi-uplifting and Digidownshifting at work.